Application of the method of hierarchy analysis for decision making in conditions of definition - Mahis Oksana (онлайн, 2020)
Person makes decisions based on known information and using a certain method every day. The hierarchy analysis method is viewed as the general theory of measurement; it is used to derive the ratio scales from both discrete and continuous pair comparisons in multilevel hierarchical structures. Comparisons can be made on the basis of real or alleged values reflecting possible preferences. The method is widely used in problems of multi-criteria decision making, strategic planning, forecasting, and even in conflict resolution problems. Moreover, it is intended for the analysis of nonlinear structures to perform both deductive and inductive inferences.
Keywords: Risks, analysis, decision making, hierarchy, criterias